The Ability To Calculate Mathematical Multiplication Using Cross Line Method - Sriyanti Mustafa; Amaluddin Amaluddin; Riska Riska (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
Elementary school students generally consider mathematics learning difficult, especially in the matter of multiplication, so a method is needed to develop and improve mathematical calculation skills. One method that can be used is the cross line method. This research aims to improve the ability to calculate multiplication using the cross line method. This type of research is Classroom Action Research (CAR) with the subject of research on third grade students of SD Negeri 9 Tanrutedong, South Sulawesi. Techniques of data collection were test and observation. The instruments used were test sheets and observation sheets. The collected data were analyzed using descriptive statistics. The results showed that the use of the cross line method could improve students' ability to calculate multiplication. This is indicated by the increase in: (1) The average score of the ability to count in the first cycle of 67.39 increased in the second cycle to 92.00, (2) The achievement of student learning completeness from the first cycle of 65.22% increased in the second cycle to 100%, and (3) the increase in the average percentage of student activity in the learning process by 77.78% in the first cycle to 94.68% in the second cycle